A Qualitative Inquiry of Improved Alliance in Hispanic Families Paired with Hispanic Therapists in Functional Family Therapy. (October 2022) - Jacob, Charles J.; Robbins, Michael; Turner, Charles
Functional Family Therapy (FFT) is an evidence-based family intervention that has demonstrated efficacy in reducing rates of re-offense and engagement with the justice system among diverse samples, including Hispanic youth and families. Past research (i.e., Flicker et al., 2008) found that Hispanic therapists matched with Hispanic clients in FFT experienced more positive outcomes than their White counterparts. We conducted a qualitative analysis of session notes completed by three Hispanic FFT therapists treating 33 Hispanic families (99 sessions) with positive outcomes. Grounded theory analysis elicited nine codes related to therapist behaviors. Implications regarding administration of FFT with Hispanic families are discussed.